GATA2 Deficiency and Epstein–Barr Virus Disease - Cohen, Jeffrey I. (Frontiers in Immunology, 2017)
GATA2 is a transcription factor that binds to the promoter of hematopoietic genes. Mutations in one copy of the gene are associated with haploinsufficiency and reduced levels of protein. This results in reduced numbers of several cell types important for immune surveillance including dendritic cells, monocytes, CD4, and NK cells, as well as impaired NK cell function. Recently GATA2 has been associated with several different presentations of severe Epstein-Barr virus (EBV) disease including primary infection requiring repeated hospitalizations, chronic active EBV disease, EBV-associated hydroa vacciniforme with hemophagocytosis, and EBV-positive smooth muscle tumors. EBV was found predominantly in B cells in each of the cases in which it was studied, unlike most cases of chronic active EBV disease in which the virus is usually present in T or NK cells. The variety of EBV associated diseases seen in patients with GATA2 deficiency suggest that additional forms of severe EBV disease may be found in patients with GATA2 deficiency in the future.